2016
DOI: 10.4103/1596-3519.188890
|View full text |Cite
|
Sign up to set email alerts
|

Induction to delivery interval using transcervical Foley catheter plus oxytocin and vaginal misoprostol: A comparative study at Aminu Kano Teaching Hospital, Kano, Nigeria

Abstract: Background:Induction of labor (IOL) is an artificial initiation of labor before its spontaneous onset for the purpose of delivery of the fetoplacental unit. Many factors are associated with its success in postdatism.Objective:To compare the induction delivery intervals using transcervical Foley catheter plus oxytocin and vaginal misoprostol, and to identify the factors associated with successful induction among postdate singleton multiparae.Materials and Methods:The study was a prospective randomized controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 19 publications
(15 reference statements)
1
19
0
Order By: Relevance
“…Of the 103 trials identified, just 63 were RCTs. 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 The majority of RCTs were single-center trials conducted in academic hospitals, which can limit the generalizability of the results to other community-based populations. Among the 12 multicenter trials, the number of centers ranged from 2 to 49 and tended to include both university-affiliated and community hospitals.…”
Section: Limitations Of Trials On Labor Inductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 103 trials identified, just 63 were RCTs. 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 The majority of RCTs were single-center trials conducted in academic hospitals, which can limit the generalizability of the results to other community-based populations. Among the 12 multicenter trials, the number of centers ranged from 2 to 49 and tended to include both university-affiliated and community hospitals.…”
Section: Limitations Of Trials On Labor Inductionmentioning
confidence: 99%
“…For example, two trials compared the Foley catheter plus oxytocin versus vaginal misoprostol. 28 70 Another compared vaginal dinoprostone with or without sequential oxytocin versus vaginal misoprostol plus sequential oxytocin. 83 These trials may have yielded more meaningful data if the combination agents were compared with the same single agents (e.g., Foley's catheter plus oxytocin vs. Foley's catheter alone or oxytocin alone).…”
Section: Limitations Of Trials On Labor Inductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of the studies included in the meta-analysis are shown in table 1. From the four included studies three were conducted in the USA, (13,(18)(19), one in Nigeria (20). In general, the included participants had singleton pregnancies with an unfavorable cervix, intact membranes, and with the fetus in cephalic presentation in the third trimester of pregnancy.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Three studies recruited primi-and multigravida women (13,(18)(19). One study enrolled only multigravida women (20) and one enrolled only primigravida women (18). Only in two studies the main outcomes were reported separately by primi and multigravidas (13,19).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%